Synthesis and spectroelectrochemistry of new phthalocyanines with ester functionalities - KOCA, ATIF (ELSEVIER SCI LTD, 2012)
Metal-free (H(2)Pc) and metallophthalocyanines (MPc: M: Co, Zn) with four n-pentyl ester of thioglycolic acid groups have been synthesized by the esterification of the corresponding carboxylic acid derivatives with n-pentanol. The novel phthalocyanine compounds were characterized by elemental analyses, mass, FT-IR and UV-Vis spectral data. The aggregation investigations carried out in different concentrations and solvents indicate that ester substituted metal-free and metallo-phthalocyanine compounds have not shown any aggregation behavior in the concentration range of about 10(-5) M. Electrochemical and in-situ spectroelectrochemical measurements give common MPc based redox behaviors which supported the proposed structure of the complexes. While CoPc gives both metal-based and ring-based redox processes, H(2)Pc and ZnPc give only ring-based electron transfer processes. In-situ electrocolorimetric method was applied to investigate the color of the electro-generated anionic and cationic forms of the complexes. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Esterification; Electrochemistry; Spectroelectrochemistry; Electrocolorimetry; DCC; ZINC PHTHALOCYANINES; METAL-FREE; IN-SITU; METALLOPHTHALOCYANINES; SUBSTITUENTS; POSITIONS; COMPLEXES; CO(II)